Control of competence by related non-coding csRNAs in Streptococcus pneumoniae R6 - Laux, Anke; Sexauer, Anne; Sivaselvarajah, Dineshan; Kaysen, Anne; Brückner, Reinhold (Frontiers in Genetics, 2015)
The two-component regulatory system CiaRH of Streptococcus pneumoniae is involved in ß-lactam resistance, maintenance of cell integrity, bacteriocin production, host colonization, virulence, and competence. The response regulator CiaR controls, among other genes, expression of five highly similar small non-coding RNAs, designated csRNAs. These csRNAs control competence development by targeting comC, encoding the precursor of the competence stimulating peptide CSP, which is essential to initiate the regulatory cascade leading to competence. In addition, another gene product of the CiaR regulon, the serine protease HtrA, is also involved in competence control. In the absence of HtrA, five csRNAs could suppress competence, but one csRNA alone was not effective. To determine if all csRNAs are needed, reporter gene fusions to competence genes were used to monitor competence gene expression in the presence of different csRNAs. These experiments showed that two csRNAs were not enough to prevent competence, but combinations of three csRNAs, csRNA1,2, 3, or csRNA1,2,4 were sufficient. In S. pneumoniae strains expressing only csRNA5, a surprising positive effect was detected on the level of early competence gene expression. Hence, the role of the csRNAs in competence regulation is more complex than anticipated. Mutations in comC (comC8) partially disrupting predicted complementarity to the csRNAs led to competence even in the presence of all csRNAs. Reconstitution of csRNA complementarity to comC8 restored competence suppression. Again, more than one csRNA was needed. In this case, even two mutated csRNAs complementary to comC8, csRNA1-8 and csRNA2-8, were suppressive. In conclusion, competence in S. pneumoniae is additively controlled by the csRNAs via post-transcriptional regulation of comC.